Profil Konsep Diri Terhadap Motivasi Belajar Siswa - Lucky Adelia Apriani; Eka Sari Setianingsih; Joko Sulianto (Universitas Pendidikan Ganesha, 2021)
There are still students who do not know the importance of the concept of self-development, lack of discipline in learning, discipline in going to class, and discipline in doing assignments. Another problem is that students do not appreciate time in doing assignments and also attending class. The purpose of this research is to analyze the profile of self-concept on the learning motivation of fifth-grade elementary school students. This type of research is qualitative research, using the methods of observation, interviews, questionnaires, and documentation. Data analysis can be done by collecting data (data collection), data presentation (data display), data reduction (data reduction), verification of conclusion drawing (conclusion drawing/verification. Research collects data in the form of research observations during research such as the results of interviews). with teachers, principals, and students. The results show that self-concept development has been implemented through habituation activities. Students are trained to be able to develop the concept of self-development in every learning activity that takes place for the formation of student character. This is very important for students to develop self so that it can achieve learning objectives. Based on the results of the study, it can be concluded that self-concept affects students' learning motivation.